Ethical Considerations in the Recruitment of Military Partners in Combat‐Related Posttraumatic Stress Disorder Research. Issue 3 (25th August 2014) - Yambo, Teresa W.; Hamilton, Rebekah; Johnson, Mary E.
<x xml:space="preserve">Abstract</x> Background The recruitment of military partners in combat‐related posttraumatic disorder (PTSD) research necessitates nurses' awareness to their unique ethical concerns. Safeguarding the ethical rights of partners living with veterans with PTSD is crucial to the development and implementation of quality, rigorous research designs. Nurses should understand the unique ethical considerations that pertain to partners' participation in PTSD research. Objective To describe the ethical considerations relating to the recruitment of partners in PTSD research. Method A succinct discussion of the recent concerns in the recruitment of military partners in PTSD research. Results The ethical guidelines of the American Psychiatric Association are employed to describe implications for researchers, educators, and administrators. For clinical nurses, the American Nurses Association's initiative to support military families is used to guide our discussion. Nurses are in a leading position to advocate for the ethical recruitment of military partners in PTSD research. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Yambo </boxed-text> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Hamilton </boxed-text> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Johnson </boxed-text>